2018
DOI: 10.1152/ajplung.00052.2018
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction decreases NF-κB signaling in fetal pulmonary artery endothelial cells of fetal sheep

Abstract: Intrauterine growth restriction (IUGR) in premature newborns increases the risk for bronchopulmonary dysplasia, a chronic lung disease characterized by disrupted pulmonary angiogenesis and alveolarization. We previously showed that experimental IUGR impairs angiogenesis; however, mechanisms that impair pulmonary artery endothelial cell (PAEC) function are uncertain. The NF-κB pathway promotes vascular growth in the developing mouse lung, and we hypothesized that IUGR disrupts NF-κB-regulated proangiogenic targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 77 publications
1
14
0
Order By: Relevance
“…They showed decreased NF-κB signaling in pulmonary artery endothelial cells (PAECs) using a sheep model for IUGR (chronic placental insufficiency). Furthermore, remarkable alterations in the expression of extracellular matrix (ECM) pathways, including decreased collagen and laminin, have been detected using microarray analysis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…They showed decreased NF-κB signaling in pulmonary artery endothelial cells (PAECs) using a sheep model for IUGR (chronic placental insufficiency). Furthermore, remarkable alterations in the expression of extracellular matrix (ECM) pathways, including decreased collagen and laminin, have been detected using microarray analysis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical findings were confirmed in experimental animal models of IUGR, showing an increase of respiratory system resistance and a reduction of lung compliance in adult rats after IUGR (6,7). Along with reduced lung function, lung structural analysis revealed impaired alveolar formation with lung growth arrest and adverse effects of angiogenesis after IUGR (6,28,48,49). Interestingly, recent studies from our group showed that low birth weight and early postnatal reduced alveolar formation after IUGR were followed not only by accelerated postnatal weight gain but also by an alveolar growth (66), as determined by measurement of mean linear intercept as an indicator of alveolarization and quantification of proliferative myofibroblasts.…”
Section: Iugr Is Intimately Linked To Aberrant Lung Development Andmentioning
confidence: 78%
“…An altered innate immune system is associated with FGR based on the increased susceptibility to infections in the postnatal period ( Amdi et al, 2020 ). Additionally, the NF-κB pathway contributes to vascular growth in the developing fetal lung, and the maintenance of endothelial NF-κB activation may be useful in FGR marked by disrupted angiogenesis ( Dodson et al, 2018 ). The significantly down-regulated gene HLA–DQA1 encodes a membrane-anchored protein for presenting peptides derived from extracellular proteins.…”
Section: Discussionmentioning
confidence: 99%